Hidden persuasion : 33 psychological influence techniques in advertising - Andrews, Marc, ....-; Van Leeuwen, Matthijs, ....-; Van Baaren, Rick, ....- (Amsterdam : BIS, 2013)
Visual messages are omnipresent in our daily life. They are constantly attempting to persuade us to buy, learn and act. Some are more successful than others in infl uencing our behavior and choices. What is the secret power of these messages? How do they succeed in changing our behavior? This book analyzes advertising beyond the persuasive power of the imagery itself. It explains the psychology behind 33 effective infl uence techniques in visual persuasion and how to apply them. The techniques range from infl uencing essentials to more obscure and insidious ones. The reader will gain deep insights into how visual means are constructed to infl uence behavior and decisionmaking on an unconscious level. All techniques are supported by rich visual references and additional information on the psychology of behavior change. This publication is not just an eye-opener for professionals and students in the communications and design fi eld, but also for anybody who wants to understand how our behavior is infl uenced unconsciously by advertising, social campaigns and governmental messages. The book is co-authored by leading fi gures in social infl uence and visual persuasion. It is designed as an accessible modern reference book for creating and understanding persuasive visual imagery. It will open your eyes, we promise!
Keywords: Reclame ; psychologie